The presence of culture in textbooks: An assessment tool for cultural items - Larrea Espinar, Ángela Mª; Raigón Rodríguez, Antonio (Círculo de Lingüística Aplicada a la Comunicación, 2020)
In recent years, the long-established relationship between language and culture has been brought back to the spotlight. This study joins the existing research on the field of cultural analysis in English language teaching materials designing a threefold checklist for the cultural analysis of language textbooks. Using this checklist and content analysis methodology, three editions of a textbook have been analysed to determine if cultural items have been gradually added to those textbooks, since the Common European Framework of Reference determines that the acquisition of cultural competence is fundamental to develop intercultural citizens. Additionally, we have examined which skill is the most commonly used to promote cultural awareness. Findings show that there has actually been a constant inclusion of cultural items to the textbooks; however, it was also found that not all the cultural aspects were equally represented, which suggests that culture learning is not comprehensive.